THE EFFECT OF POLITICAL BUDGETING ON IMPROVING THE QUALITY OF POLITICAL EDUCATION IN SOCIETY: A LITERATURE REVIEW - Melyana R Pugu; Edy Sijaya (Adisam Publisher, 2025)
This paper discusses the influence of political budgeting in supporting the improvement of the quality of political education in the community through literature analysis. Political education plays an important role in creating a society that is aware of its rights, obligations and responsibilities in a democratic system. The provision of a political budget is considered a fundamental element to support the implementation of political education programmes, such as training, seminars and counselling. The study results show that adequate budget allocations can improve public access to political information and strengthen active participation in the democratic process. However, the effectiveness of budget provision is influenced by transparent and accountable management. The risk is that the budget may not be targeted if there is misuse or certain political interests. Therefore, political budgeting has great potential to improve the quality of political education if accompanied by good management and consistent policy support.